2000
DOI: 10.1161/01.str.31.10.2301
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Flavonoids, Carotenoids, Vitamins C and E, and Risk of Stroke in Male Smokers

Abstract: Background and Purpose-Antioxidants may protect against atherosclerosis and thus prevent cerebrovascular disease. We studied the association between dietary antioxidants and subtypes of stroke. Methods-The study cohort consisted of 26 593 male smokers, aged 50 to 69 years, without a history of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 29 publications
4
156
3
4
Order By: Relevance
“…Generally, risk of stroke has not been as strongly associated with dietary and lifestyle factors as has risk of CHD, despite the association of incidence of stroke with hypertension and serum lipid abnormalities (Leys et al, 2002). Some studies have reported lower risk of ischemic stroke with higher consumption of green leafy vegetables (Joshipura et al, 1999;Johnsen et al, 2003;Sauvaget et al, 2003) or with higher consumption of total vegetables (Hirvonen et al, 2000). However, this association has not always been independent of known CVD risk factors (Johnsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, risk of stroke has not been as strongly associated with dietary and lifestyle factors as has risk of CHD, despite the association of incidence of stroke with hypertension and serum lipid abnormalities (Leys et al, 2002). Some studies have reported lower risk of ischemic stroke with higher consumption of green leafy vegetables (Joshipura et al, 1999;Johnsen et al, 2003;Sauvaget et al, 2003) or with higher consumption of total vegetables (Hirvonen et al, 2000). However, this association has not always been independent of known CVD risk factors (Johnsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Their wide distribution throughout the plant kingdom results in their inevitable presence in diets rich in plant-derived foods or beverages, where they appear to contribute to the overall health benefits of consuming such a diet. The epidemiological link of flavonoid intake to prevention of diabetes appears to be the strongest thus far (Nicolle et al, 2011), however specific links of flavonoid intake to cardiovascular mortality, chronic inflammation, cancer and other conditions are also evident (Arab and Liebeskind, 2010;Hirvonen et al, 2000;Manthey, 2000;Mink et al, 2007;Steinmetz and Potter, 1996).…”
Section: Introduction: C-glycosylation Of Flavonoidsmentioning
confidence: 99%
“…Several studies have suggested that dietary antioxidants may play a protective role against the development of subarachnoid hemorrhage (SAH) (Marzatico et al, 1998;Leppala et al, 1999Leppala et al, , 2000Hirvonen et al, 2000;Kaynar et al, 2005;Okamoto, 2006;Okamoto and Horisawa, 2006). In general, various dietary antioxidants may be interactive or synergistic rather than isolated.…”
Section: Introductionmentioning
confidence: 99%